PENGUATAN KARAKTER ANAK MELALUI NYANYIAN BERBASIS BUDAYA - Tarwiyah Adi, Tuti (Program Studi Pendidikan Musik, 2021)
This paper is a study on Strengthening Children's Character through Culture-Based Singing. The background of the research is the lack of children's songs that contain character values ​​as well as culture-based. In fact, culture-based children's songs, apart from being able to educate, can also shape and strengthen children's character which is very much needed during the pandemic and welcomes the era of society 5.0. The purpose of this study was to identify and analyze children's songs that contain cultural-based character values. Data collection is taken from books, youtube, and other related sources. The method used is descriptive qualitative with an emphasis on literature study. The results showed that from 55 children's songs collected and analyzed, at least each song contained two aspects of character values. Furthermore, ten songs were selected that contain the most elements of character values, which on average have at least 5 aspects of character values. The songs are Ride the Delman, See My Garden, The Shepherd Child, Plant Corn, Take the Train, Becak, Go To The Sea, Uncle Comes, Wake Up, and Go To Study. There are only six songs that actually contain cultural values, especially local wisdom, namely: I am a Shepherd Child, Becak, Beramai to the Sea, Ride Delman, Ride the Train, and Uncle comes. Therefore, the government through the Ministry of Education and Culture must promote the socialization of songs containing character values ​​as well as promote the creation of children's songs containing cultural-based character education which is very much needed at this time to strengthen children's character while preserving Indonesia's cultural wealth.